Lord Shiva’s Timelessness against Temporality: A Study of A River Sutra - BHATNAGAR, MAMTA (International Journal of Psychosocial Rehabilitation, 2020)
Mythological stories are the documents of a culture as they touch almost everything we feel and experience. Myths came even before art, language, literature, religion, science and philosophy and have survived the test of time today. Therefore, they throw light on people’s collective unconscious from the pre-historic to the contemporary era; hence, they are a powerful tool for understanding the way of living and psychology of a particular group. Gita Mehta, in her novel, A River Sutra, has narrated the happenings viewing them from the point of view of the myths related to Shiva and the holy river Narmada. The characters of the novel are common human beings like tribals, researchers, musicians, ascetics. pilgrims etc. for whom the Narmada and its folk tales have been the focus of the lives of such people since time immemorial. As the river is the mythological daughter of Shiva, the novel revolves around the latter’s myths and his association with the earthly life. The present paper is an attempt to explore Gita Mehta’s use of the elements of Shiva’s timelessness in A River Sutra. Simultaneously, in the same pursuit, it aims to study the association of Shiva’s mythology in the context of the contemporary Indian society and human beings at large.